Heat flux measurement, a tool for laser beam welding process monitoring – preliminary study - Mityakov, Andrey; Salminen, Antti; Piiroinen, Aki; Ward-Raatikainen, Henry (United Kingdom, 2026)
Accurate measurement of reflected heat flux in laser welding is critical for process monitoring but remains challenging due to the limitations of traditional techniques. This study introduces transverse heat flux sensors (THFS) based on the Seebeck effect in bismuth single crystals, enabling real-time measurements with nanosecond response times. Experiments were conducted at 1.5 kW (conduction), 5.5 kW (transition), and 9.5 kW (keyhole) power settings. Results showed distinct heat flux differences: 1.25 kW/m2 with ±0.25 kW/m2 fluctuations in conduction mode, decreasing to 500 W/m2 with ±80 W/m2 fluctuations in keyhole mode. Two THFS – one fixed above the focal point and one movable – were used to explore spatial heat flux distribution. This study demonstrates the feasibility of THFS for laser welding monitoring, paving the way for advanced process control through numerical simulations and machine learning.
20th Nordic Laser Materials Processing Conference